RESEARCH ON TRAINING SYSTEM OF PRODUCT DESIGN MAJOR BASED ON NEW DESIGN REQUIREMENTS (Proceedings of the International Conference on Education, 2021)
With the advent of the industry 4 and the Internet plus era, the industrial structure of various industries is also constantly upgrading. As a major closely integrated with the industry, the characteristics of product design are also changing. But at present, some colleges still use the previous student training system, not keeping up with the pace of the development of the times, nor adapting to the social demand for design talents. As teachers engaged in design education, the author has the responsibility to re-examine the new needs of various industries for design, reasonably reform the student training system, and improve the applicability of the training system. Through understanding the changes of the times' needs and qualitative analysis of the latest requirements of current enterprises for designers, the author deeply analyzes the existing training system of product design specialty, and from the perspective of system, reestablishes the ability requirements and knowledge requirements of product design specialty through questionnaire survey, and divides the training system into several ability modules and knowledge modules, And determine the ability and knowledge to be cultivated in each stage of the University. The goal of the new student training system is very clear, the key ability and knowledge have been strengthened, and the curriculum has also been improved
Keywords: demand; product design; modular